Coping with noxious effects of quinine by praying mantids (Mantodea) and spiders (Araneae). (15th April 2019) - Mebs, Dietrich; Wunder, Cora; Toennes, Stefan W.
Abstract: Because of its bitter taste, quinine elicits strong antifeedant and toxic effects in animals including arthropods. In the present study, two mantis, Sphodromantis viridis, Hierodula membranacea, and two spider species, Nephila edulis, Selenocosmia javanensis, were offered a quinine solution or prey (crickets) contaminated or injected with quinine, which they ingested and survived without apparent toxic symptoms. Analysis of their faeces and, in the case of spiders, of silk from their web revealed that quinine was excreted over a period of 8–12 (mantids) or 7 days (spiders). Interestingly, the silk glands of the spiders served as an additional excretory organ of quinine. Both, mantids and spiders were shown to tolerate high amounts of quinine in their prey. Obviously, the bitter taste of this compound is not perceived by their gustatory receptors and consequently triggers no aversive reactions. Highlights: Taste perception of harmful compounds is essential for survival. The bitter taste of quinine usually elicits aversive reactions. Mantids and spiders were shown to cope with high amounts of quinine. Quinine is excreted in faeces and web silk. Bitter taste perception seems to be highly variable in arthropods.